Analysis of Buttering Method on Mechanical Properties Welded Material Low Carbon Steel - Dwi Winarto, Gathot; Wardhani, Rivai; Syarif, Irsyadus (Institut Teknologi Sepuluh Nopember, 2014)
In manufacturing, especially offshore, welding is one of the joining processes (steel) with very tight specification. Preparation time (fitting) both steel material which will be connected, especially when the material cutting process does not allow for mistakes, so when they do tuning of both material be spliced happen distance (gap) in excess of the standard, then the buttering method that does not eat a lot of time, wasted materials and dimensions of objects so it still makes tolerance in otherwise require. Buttering is the adding process of material in welding. It is applied on one or both sides to be connected, with the aim of giving the distance (gap) between the two materials will be in connection with welding processes meet the requirements of the standard (ASME Sec IX, 2010)1. This study aimed to indicate the effect of the buttering in welding. And the variety of wide buttering is 10 mm, 15 mm, and 20 mm. Material will be joined with welding process Shield Metal Arc Welding (SMAW). In the test, material is low carbon steel type SA 36. Tests performed were tensile test, impact test, and the test macro etching. By those tests, will be Investigated what the differences between welding without buttering and with buttering. And the final results showed the addition of wide buttering decreased tensile strength, which declines in linear: buttering width 10 mm = 413.47 MPa , buttering width 15 mm = 397.48 MPa , buttering width 20 mm = 390.07 MPa. In impact strength, it increased, which increasing linear: width 10 mm = 1.82 J/mm², 15 mm width buttering = 1.90 J/mm², 20 mm width buttering = 1.94 J/mm². And in macro test, it was shown that a Heat Affected Zone (HAZ) in buttering spread larger than HAZ in material without buttering.